Association of serum miR-99a level and metabolic dysfunction-associated steatotic liver disease, serum mTOR levels in patients with type 2 diabetes mellitus - Zhang, Yangyang; Zuo, Yuqiong; Chen, Qian; Cui, Yaqiang; Bao, Yanxia; Jiang, Panpan; Liu, Jing; Quan, Jinxing; Liu, Juxiang (Frontiers in Endocrinology, 2025)
PurposeThis study was designed with the goal of exploring miR-99a expression in T2DM patients suffering from comorbid MASLD and clarifying the importance of miR-99a in this pathological context.MethodsA total of 137 subjects were included in this study, including 50 T2DM patients with MASLD (T2DM +MASLD group),48 T2DM patients without MASLD (T2DM group), and 39 healthy subjects (Control group). We measured the levels of IL-6, mTOR and SOD in the serum of the subjects by ELISA. The plasma miR-99a levels was detected by RT-PCR. The correlation between serum miR-99a level and other indicators was analyzed.ResultsSerum miR-99a levels (median 0.79 vs 0.16 vs 0.03, P < 0.001) were significantly lower in the T2DM group than the healthy population and further decreased in the T2DM with MASLD patients (P < 0.001). After adjusting for age, gender, illness duration and BMI, spearman correlation analysis showed that TG, HbA1c, FPG, HOMA-IR, Hs-CRP, IL-6, HDL-C, mTOR(P < 0.05) remained independently linked with serum miR-99a. And stepwise linear regression analysis showed that HbA1c, IL-6 and mTOR are independent serum miR-99a correlation variables (P < 0.05). Moreover, the ROC results indicated that serum miR-99a has a high diagnostic value for T2DM with MASLD. In conclusion, serum miR-99a may be utilized as a screening biomarker for T2DM with MASLD.ConclusionsThese data highlight a potential role for miR-99a as a regulator of the comorbid incidence of T2DM and MASLD, suggesting that measuring the levels of miR-99a can effectively predict the risk of MASLD in those with T2DM.